The Existence of Beliefs in the Circle of Official Religions in Indonesia - Septiadi, Muhammad Andi; Ramdani, Zulmi (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: The religious teachings of ancestors, commonly referred to as